2017
DOI: 10.5604/12321966.1234048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antibiotic susceptibility of <i>Legionella pneumophila</i> isolated from water systems in Poland

Abstract: obtained from water systems in public buildings in Poland were tested. Susceptibility testing was performed using the E-test method. The tested antibiotic were azithromycin, ciprofloxacin, and rifampicin. The medium used for the susceptibility testing was BCYE-, a special medium for Legionella cultivation. Results. Among the tested strains, L. pneumophila was the only one resistant to azithromycin. It was a strain of L. pneumophila SG 2-14 isolated from the water system in a sanitorium. All isolates were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Xiong et al have reported the increased effectiveness of levofloxacin [ 45 ], followed by minocycline and doxycycline. The effectiveness of quinolones—ciprofloxacin, this time—was recorded in a later study by Sikora A. et al [ 46 ]. Contrary to these findings, it was Sharaby et al [ 30 ] who revealed some slight resistance against quinolones but an effectiveness of doxycycline, clarithromycin, rifampicin and trimethoprim sulphamethoxazole (SXT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiong et al have reported the increased effectiveness of levofloxacin [ 45 ], followed by minocycline and doxycycline. The effectiveness of quinolones—ciprofloxacin, this time—was recorded in a later study by Sikora A. et al [ 46 ]. Contrary to these findings, it was Sharaby et al [ 30 ] who revealed some slight resistance against quinolones but an effectiveness of doxycycline, clarithromycin, rifampicin and trimethoprim sulphamethoxazole (SXT).…”
Section: Resultsmentioning
confidence: 99%
“…In 8/89 (9%) of the articles, the authors used the Kirby–Bauer method and followed the protocol proposed by the CLSI ( Table S1 raw data; [ 82 , 83 ]) or older citations ( Table S1 raw data; [ 40 , 84 ]). Finally, there were 9/89 (10%) articles that applied a combination of the methods ( Table S1 raw data; [ 42 , 46 , 56 , 65 , 85 , 86 , 87 , 88 , 89 ]) and one multi-center study from Dunbar et al 2007 [ 90 ]. In the Dunbar et al [ 90 ] study, they performed an alternative Broth Microdilution method (Sensititre microtitre plates containing freeze-dried antimicrobial agents) in order to evaluate the activity of telithromycin against a worldwide L. pneumophila isolate set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those that specifically investigated Legionella spp., two studies referenced the International Organization for Standardization (ISO) 11731—water quality enumeration of Legionella [ 31 , 36 ]. One study investigating L. pneumophila followed Italian guidelines for prevention and the control of legionellosis [ 34 ] and two studies used other culturing techniques [ 35 , 44 ]. Of the studies investigating P. aeruginosa, four papers used membrane filtration methods followed by plating onto selective media such as R2A, cetrimide, and Columbia with horse blood, one of which referenced the ISO 16266:2008—detection and enumeration of P. aeruginosa specifically [ 38 , 39 , 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of nosocomial infections is very low (7), but it represents a major public health concern mainly because nosocomial cases occur in a significant proportion in patients without any specific risk factor, and also due to the high lethality (50% in the Valencian Community, Spain). (8,9) The presence of bacteria in water is considered a prerequisite for infection (10,11). The growth of Legionella depends on several factors, among others, pH and hardness of the water, presence of old pipes, standing water, difficulty in maintaining the right temperature, biofilm formation, and the pipe length as an indirect factor (12) (13).…”
Section: Introductionmentioning
confidence: 99%